2017
DOI: 10.1039/c7mb00276a
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained simulations of conformational changes in the multidrug efflux transporter AcrB

Abstract: The multidrug resistance (MDR) system actively pumps the antibiotics out of cells causing serious health problems. During the pumping, AcrB (one of the key MDR components), undergoes a series of large-scale and proton-motive conformational changes. Capturing the conformational changes through all-atom simulations is challenging. Here, we implement a hybrid coarse-grained force field to investigate the conformational changes of AcrB in porter domain under different protonation states of Asp407/Asp408 in trans-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…Thus, it is important to understand the molecular details of how Slp4-a triggers the pre-fusion for the exocytosis process. In this work, we conducted MD simulations using the hybrid PACE (protein in atomistic details coupled with a coarse-grained environment) force field [ [23] , [24] , [25] ] to examine the Ca 2+ -dependent response of Slp4-a. POPE is used as lipid membranes to study the interaction between Slp4-a and lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to understand the molecular details of how Slp4-a triggers the pre-fusion for the exocytosis process. In this work, we conducted MD simulations using the hybrid PACE (protein in atomistic details coupled with a coarse-grained environment) force field [ [23] , [24] , [25] ] to examine the Ca 2+ -dependent response of Slp4-a. POPE is used as lipid membranes to study the interaction between Slp4-a and lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies regarding the interaction between RND transporters and their substrates/inhibitors (see reference 8 for a recent review) have provided useful insights into the molecular determinants of polyspecificity (8,(40)(41)(42)(43)(44), the mechanisms of active transport of substrates (8,(45)(46)(47)(48)(49)(50), and the putative inhibition or modulation of transport routes (20,22,(51)(52)(53)(54). In particular, studies performed by the authors identified key structural determinants discriminating between substrates and inhibitors of AcrB in Escherichia coli (41), which were later confirmed by experimental findings (22).…”
mentioning
confidence: 99%
“…It would be interesting to check whether drugs binding in state A could bind to state M‐A. If we presume that changes in the TM domain are due to the protonation, the value and fusion values of the clusters could suggest that either the kinetics of the protonation differ, or the number of protons differs (this number is still under debate even for AcrB) 14,39,40,54 …”
Section: Discussionmentioning
confidence: 99%